The wedding dress in Costa Rica: practices, symbolism, and persistence of traditions (2016-2023) - González Quesada, Angie (2025)
This article presents the results of anthropological research on the practices andsymbolism of the wedding dress in Costa Rica between the years 2016 and 2023. Thepurpose is to analyze the meanings of the wedding dress for Costa Rican society;acquisition practices of female marriage trousseau and associated religious symbolism are studied. A brief historical review of the origin of the use of the trousseau ispresented. Qualitative methodology and ethnographic method were used.